Interaction in written texts: A bibliometric study of published research - Hyland , Ken; Jiang, Feng (Kevin) (Studies in Second Language Learning and Teaching, 2023)
While writing involves interactions between writers and readers as each considers the other in creating and interpreting texts, research interest in written interaction is a fairly recent development. This paper uses a bibliometric analysis to trace the growing interest in written interaction over the past 30 years from its origins in philosophy, conversation analysis and sociocultural language pedagogy. To do so, we analyzed all 918 articles mentioning writing and interaction in the social science citation index since 1990, dividing the corpus into two periods following the massive increase in interest after 2005. We identify which topics have been most prevalent and which authors, publications, journals and countries most influential over time. The results indicate the growing importance of identity, genre, discipline, metadiscourse and stance, particularly drawing on corpus methods. We also note the participation of authors from more countries in publishing interaction research with the growth of authors from China becoming particularly visible. These findings may interest those working in written discourse analysis and scholarly publishing.